Peningkatan Kapasitas Financial Report Kspps Az-Zahra Wonoayu Sidoarjo Melalui Pendekatan Community Based Research - Rosyidah, Norma (Proceedings of Annual Conference on Community Engagement, 2022)
Nowdays, Islamic financial institutions (LKS) are developing very rapidly, one of which is the Sharia Savings and Loans Cooperative (KSPPS). Its existence is needed by the community because it provides loans with low margins to meet both consumptive and productive needs. The purpose of this service is to provide training in preparing financial reports using the Community Based Research (CBR) method. This method has the advantage that problems are found together with groups and researchers, so that solutions can be mutually agreed upon. The results of the observations found three problems, namely non-performing financing, not holding the Annual Member Meeting (RAT) and lack of knowledge and skills in preparing reports. Solutions were found jointly between researchers and KSPPS administrators. During the assistance, the management and supervisors of KSPPS Az-Zahra were very enthusiastic in participating in the training, and financial reports were prepared annually until the financial statements were balanced.